Prayers, Protest, and Police: How Religion Influences Police Presence at Collective Action Events in the United States, 1960 to 1995. (December 2015) - Beyerlein, Kraig; Soule, Sarah A.; Martin, Nancy
Do police treat religious-based protest events differently than secular ones? Drawing on data from more than 15, 000 protest events in the United States (1960 to 1995) and using quantitative methods, we find that law enforcement agents were less likely to show up at protests when general religious actors, actions, or organizations were present. Rather than reflecting privileged legitimacy, we find that this protective effect is explained by religious protesters' use of less threatening tactics at events. When religion is disaggregated into different traditions, only mainline and black Protestant groups have lower rates of policing than secular groups. As with the general religion finding, the buffering effect these traditions have on policing is mediated by protester tactics. Moreover, we find that fundamentalist Christians are more likely to be policed than are secular activists when threatening tactics are included. Finally, when actors associated with non-Christian religions engage in extremely confrontational tactics, they are more likely to provoke a police response than are similarly behaving secular groups.